2020
DOI: 10.3390/su12176983
|View full text |Cite
|
Sign up to set email alerts
|

Dry Port Terminal Location Selection by Applying the Hybrid Grey MCDM Model

Abstract: Globalization and decentralization of production generate the intensive growth of goods and transport flows, mostly performed by the maritime transport. Ports, as the main nodes in the global logistics networks, are becoming congested, space for their expansion limited, and traffic in their hinterland congested. As a solution to these and many other hinterland-transport-related problems stands out the development of dry port (DP) terminals. Selection of their location is one of the most important strategic dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 83 publications
0
29
0
Order By: Relevance
“…MCDM models are frequently developed to support decision-makers in solving complex multicriteria decision-making problems in different industries and sectors. These decision-making problems include location selection [17][18][19], material selection [20,21], and asset allocation [22]. Among these, many MCDM models have been developed to solve supplier evaluation and selection problems of different supply chains in various industries.…”
Section: Mcdm Methods and Applicationsmentioning
confidence: 99%
“…MCDM models are frequently developed to support decision-makers in solving complex multicriteria decision-making problems in different industries and sectors. These decision-making problems include location selection [17][18][19], material selection [20,21], and asset allocation [22]. Among these, many MCDM models have been developed to solve supplier evaluation and selection problems of different supply chains in various industries.…”
Section: Mcdm Methods and Applicationsmentioning
confidence: 99%
“…In this paper, the selection of the most suitable system using Multi-Criteria Decision Making (MCDM) analysis has been made. Based on the literature review, the Analytical Hierarchy Process (AHP) method was found to be the most commonly used method for numerous construction-related decisions, as well as in the case of the determination of the weights of different indicators or criteria for sustainability ratings [4,19,[30][31][32][33][34][35][36][37]. Next to AHP, studies also commonly used the Delphi model, Simple Additive Weighting (SAW), the TOPSIS method or other MCDM techniques, and combinations of them for decision-making or ranking [38][39][40][41][42][43].…”
Section: Methodsmentioning
confidence: 99%
“…Having in mind that the profitability of IT mainly varies according to the analyzed flows, state of the market, spatial and geographic characteristics and logistics systems development degree, it is important to define the development direction of the DP concept and the IT system as well [36]. More or less, all regions of the world have been analyzed through the concept of DP [37][38][39][40][41][42][43], therefore several research articles covering this topic for the region of Southeastern Europe exist as well [44][45][46][47][48]. The main advantage of the DP concept in the context of IT network modelling is its adaptiveness and configurability to different structures of IT systems, geographical regions, and different goods flow categories.…”
Section: Treatment Of It In the Scientific Literature And Its Status In Southeastern Europementioning
confidence: 99%